EARTHQUAKE LOCATION INFORMATION AND MAP APPLICATIONS BASED ON ANDROID (GEUMPA) - Ilham Zulfikri; Akhyar Lubis; Eko Haryanto (Sean Institute, 2022)
Indonesia as an archipelago that lies in meeting the world's three major plates of the Australian Plate, Eurasian, and Pacific lead this country susceptible to earthquakes. Therefore, the need for a reliable earthquake information is required. For portability problem, one way to get earthquake information is to use portable devices such as smartphone or the tablets. Android as an operating system that can be embedded in portable devices, can also be installed a variety of applications required by users. At the end of this project developed an application of information and maps of earthquake locations named “Geumpa”. This application is expected to be an alternative as an option for use applications on the Android – based devices, especially for users of Android in Indonesia, because Indonesia lies that include prone to earthquake.